Congenital long QT syndrome: A challenging diagnosis by fetal echocardiography - Aura Daniella Santi; Miguel Restrepo (Wolters Kluwer Medknow Publications, 2022)
The diagnosis of long QT syndrome (LQTS) in utero presents many challenges for clinicians, and there is high risk for intrauterine fetal demise as life-threatening arrhythmias develop secondary to QT prolongation. We describe a challenging case of a fetus presenting with sinus bradycardia and second-degree atrioventricular block with episodes of ventricular tachycardia. A prenatal diagnosis of LQTS was suspected given the fetal echocardiographic findings of a short ventricular relaxation time, due to extremely prolonged refractory period. The patient was delivered emergently due to Torsade's with hydrops, with ongoing arrhythmia despite medical management requiring implantation of pacemaker and sympathectomy. Early recognition of LQTS is important to optimize fetal survival with prompt medical management.